2017
DOI: 10.1074/jbc.m116.767699
|View full text |Cite
|
Sign up to set email alerts
|

Residues in the RecQ C-terminal Domain of the Human Werner Syndrome Helicase Are Involved in Unwinding G-quadruplex DNA

Abstract: The structural and biophysical properties typically associated with G-quadruplex (G4) structures render them a significant block for DNA replication, which must be overcome for cell division to occur. The Werner syndrome protein (WRN) is a RecQ family helicase that has been implicated in the efficient processing of G4 DNA structures. The aim of this study was to identify the residues of WRN involved in the binding and ATPase-driven unwinding of G4 DNA. Using a c-Myc G4 DNA model sequence and recombinant WRN, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…Many in vitro and in vivo studies have shown that specialized helicases play essential roles in eliminating G4 obstacles and allowing DNA replication to continue, such as DinG , RecQ , BLM , WRN , FancJ and Pif1 . However, emerging evidences indicate that TLS DNA Pols may play key roles on the replication stalling sites caused by G4 structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many in vitro and in vivo studies have shown that specialized helicases play essential roles in eliminating G4 obstacles and allowing DNA replication to continue, such as DinG , RecQ , BLM , WRN , FancJ and Pif1 . However, emerging evidences indicate that TLS DNA Pols may play key roles on the replication stalling sites caused by G4 structures.…”
Section: Discussionmentioning
confidence: 99%
“…The signal of the first phase increasing with a fast rate (k 1 ) corresponds to replication of the 5-nt ssDNA linker, and the signal of the second phase increasing with a slow rate (k 1 0 ) corresponds to the replication of the remaining G4 structure. G4 obstacles and allowing DNA replication to continue, such as DinG [16,17], RecQ [18], BLM [21][22][23], WRN [19][20][21], FancJ [11][12][13] and Pif1 [14,15]. However, emerging evidences indicate that TLS DNA Pols may play key roles on the replication stalling sites caused by G4 structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The G4 unfolding mediated by helicases contains several steps that accompany structural rearrangements of both G4 and proteins [49,50]. The c-MYC G4 interaction with two human RecQ helicases (Werner syndrome protein (WRN) and Bloom syndrome protein (BLM)) was studied independently [51,52]. The RecQ C-terminal (RQC) domain of WRN was subjected to titration with non-G4 DNA or G4 DNA, and the residues which showed G4-specific responses were identified [51].…”
Section: G4-protein Interactionmentioning
confidence: 99%
“…The 13 amino acid RSM motif of DHX36 interacts with G4 structures [104] and a solution structure shows a DHX36 peptide including the RSM interacting with the exposed face of a tetrad in a parallel G4DNA [105]. Residues in the RecQ-C-terminal domain of WRN helicase involved in interaction with G4DNA have also been identified [106], and G4DNA docks into the same position as dsDNA with good complementarity in a structure of RecQ [107]. …”
Section: Unanswered Questionsmentioning
confidence: 99%